A child-friendly urban street criteria for Jonker walk - Sani, Safiah Syazana; Zakariya, Khalilah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
A street is a public facility adjoining buildings of which users may freely assemble, interact and move about. It plays an important role in tourism, as it connects and brings people together. Hence, this study is about a child-friendly urban street in Jonker Walk. The lack of safety features for children can be seen at this place. Plus, there is an absence of restriction to travel with children in a busy street. The aim of this study is to recommend design guidelines for a child-friendly street. There are three objectives for this research. The first one is to study a good child-friendly urban street design. The second one is to identify the difficulties faced by the children while visiting the place. The third objective is to outline a good childfriendly urban street design. This study takes place in Jonker Walk, Malacca. Observation and interviews are conducted on the street to collect data from the tourists. The expected findings will help to make a good child-friendly street design at Jonker Walk. As for the conclusion, this study will help in promoting tourism in Malacca, especially in Jonker Walk and enhance the street design to promote child-friendly tourism.